Estudio de viabilidad técnica para implementación de paneles solares en Riohacha. (2022)
Colombia has a high percentage of communities which do not have a constant or quality energy service, being one of the causes that makes it difficult for these communities to carry out their daily activities. Some of the communities that present this type of problem are found in Riohacha la Guajira. For this reason, through a technical feasibility study, the implementation and use of renewable energies through a solar panel system is sought. Taking advantage of the geographical location of Colombia, a large amount of solar energy can be obtained, which is one of the most abundant and clean, making use of this constant energy can be generated thanks to the implementation of photovoltaic solar panels with which it is sought to supply the energy service in the communities, facilitating daily tasks such as agriculture, education, among others, providing a better quality of life.